Error Reduction in Specimen Processing of Irretrievable Body Fluids. (28th October 2020) - Gannon, V; Albright, T; Wells, T; Cahak, C; Harrington, A M; Buchan, B; Ledeboer, N; Kloc, W
Abstract: Introduction/Objective: A lack of standardized processes for laboratory handling of irretrievable body fluid specimens, such as cerebrospinal fluid, serous fluids, synovial fluids, and aspirates, can result in failures that put the patient at risk by delaying testing results and/or requiring specimen recollection. We noted increased patient safety issues with irretrievable specimens in our laboratory and implemented a process improvement plan to mitigate patient harm. Herein, we report our findings of this intervention. Methods: A task force was organized with wide representation across the laboratory to design a new workflow for irretrievable specimens. Hospital Patient Safety Reporting data was used to identify flaws in the pre-analytical processes pre-intervention and to monitor effectiveness of process change, post-intervention. Our intervention consisted of developing a standardized pre-analytical process for both technical and non-technical staff that could be enforced through consistent and proper training, with well-defined responsibilities for each department involved including specimen processing, microbiology, hematology, and chemistry. Our process included a centralized sterile processing location within the Micro department as well as a standardized sample log in and sample distribution process that incorporated a chain of custody form. Results: Pre-intervention, we had 23 patient safety reports during a 3-month period (5-10/month; average 8/month) on irretrievable specimens; post-intervention, we had 9 patient safety reports over a 5-month period (0-4/month; average 2/month). Pre-intervention, failures identified included inconsistent workflows and training among staff, the absence of established protocols, and inadequate communication. Post-intervention, failures were noted due to improper and inconsistent training (n=4) or deviation from the established procedure by staff members. These failures were investigated and addressed through retraining or corrective actions as needed. Conclusion: Our data shows that the implementation of a standardized process within the laboratory significantly decreases patient safety events by improving testing turn-around-times and quality of results and by preventing the need for specimen recollections.